(untitled) (Edma 0-6: Educación Matemática en la Infancia, 2021)
The education system in United States of America is undergoing significant changes. The implementation of the new Common Core Standards in K - 12 provides for a unified structure for the entire territory. This article presents examples of how to work those new standards for mathematics in a bilingual kindergarten classroom. The implementation differs from State to State. In this specific case we follow a very strict curriculum, which includes learning materials and teacher guides. Nevertheless, teachers can always complement the curriculum with any other mathematic workshops and games. Art, board games and motor activities, among others, can help students understand - and more importantly - to apply the mathematic skills learned.